Effects of Socio-Affective Strategies on Students’ Self-Confidence in Classroom Speaking Activities - Abdul Muin; Aswati Aswati (English Education Department, 2019)
This research was to investigate the implementation of socio-affective strategies to improve students’ self-confidence in classroom speaking activities. This research was conducted in two cycles. The subjects of this study were the students of this school grade VIII A. The number of the subjects was thirty-five students. The instruments which are used to collect the data are observation questionnaire and field note. The student who had a strong desire in cycle I was 23 students, in cycle II was 33 students. The student who used visual contact in cycle I was 21 students, in cycle II was 28 students. The student who spoke aloud in cycle I was 22 students, in cycle II was 29 students. The student who used their gestures in cycle I was 24 students, in cycle II was 29 students. The student who comprehended the material in cycle I was 28 students, in cycle II was 32 students. Based on the results of the research, it can be concluded that using Socio-affective strategies can improve students’ self-confidence in speaking English